2011
DOI: 10.4103/1319-3767.87183
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in males with hepatitis C virus: Relevance to histopathologic changes and peginterferon treatment

Abstract: Background/Aim:The frequency of sexual dysfunction (SD) is not well known in patients with chronic hepatitis C virus (HCV). In spite of the fact that histological benefits of peginterferon (Peg-IFN)/ribavirin therapy are well established, the effects on sexual health are less certain. To assess the prevalence of the SD and explore its relevance to histopathologic changes and Peg-IFN treatment.Materials and Methods:The study included 100 HCV males; all the patients completed questionnaires to assess their sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
0
11
2
Order By: Relevance
“…Previous studies in the general population 33,34 and in CHC patients 3,14,31 have demonstrated that older age is a risk factor for SD. This study found that older age was associated with SD only among men.…”
Section: Rev Soc Bras Med Trop 47(5):564-572 Sep-oct 2014mentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies in the general population 33,34 and in CHC patients 3,14,31 have demonstrated that older age is a risk factor for SD. This study found that older age was associated with SD only among men.…”
Section: Rev Soc Bras Med Trop 47(5):564-572 Sep-oct 2014mentioning
confidence: 93%
“…Chronic infection with hepatitis C virus (CHC) is a worldwide health problem that affects approximately 160 million people 2 . Sexual transmission of the hepatitis C virus (HCV) has been thoroughly investigated; however, studies of SD and satisfaction with sexual life among CHC patients are scarce 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Similar prevalence of sexual dysfunction in male patients 22% was seen in the study conducted by El-Atrebi KA et al 18 Sorrel JH et al reported that in his study females were having more sexual dysfunction as compared to males. 19 Fábregas BC et al also showed association of female gender with sexual dysfunction.…”
Section: Discussionmentioning
confidence: 52%
“…Sexual dysfunction reached more than 70% during the treatment, particularly in patients over 40 years old. In addition, the affection of sexual activity varied in relation to the liver status (El‐Atrebi et al ., ). According to Hofny et al ., about one‐third of patients in mid‐thirties were diagnosed with primary infertility.…”
Section: Introductionmentioning
confidence: 97%